الآثارالتنظيمية لتطبيق نظام إدارة الجودة في المؤسسات الإقتصادية دراسة حالة:المؤسسة الوطنية للدهن وحدة سوق اهراس - هاجر منصوري; ليلى ذيب (My University, 2022)
In this study we discussed the effects of the quality management system on the organisation process inthe economic institution ,wich is a system based on specific foundation and standards in order to achieve a modern administrative system and this is considered a challange for the organizational process in the institution. Where a field study was carried out in an economic institution she holds the ISO certificate at the level of the state of souk ahras ,and the results showed a positive impact of adopting the quality management system on the organization in all aspects and department ,even to varying degrees and differences in these effects between the studied institution and the vocabulary of the organization ..................................................................... تطرقنا في هذه الدراسة الى الأثار التي تتركها نظام إدارة الجودة على عملية التنظيم في المؤسسة الإقتصادية الذي يعتبر نظام يقوم على أسس ومعايير محددةوذلك من أجل تحقيق نظام إداري حديث وهذا يعتبر بمثابة التحدي بالنسبة للعملية التنظيمية في المؤسسة . حيث تم القيام بدراسة ميدانية في مؤسسة إقتصادية حاصلة على شهادة الإيزو على مستوى ولاية سوقأهراس وبينت النتائج وجود أثر إيجابي لتبني نظام إدارة الجودة على التنظيم في جميع الجوانب والأقسام ولو بدرجات متفاوتة وإختلاف في هذه الأثار بين المؤسسة المدروسة ومفردات التنظيم .